Trabeculectomy With Antimetabolite Agents for Normal Tension Glaucoma: A Systematic Review and Meta-Analysis - Lai, Chin; Shao, Shih-Chieh; Chen, Yi-Hung; Kuo, Yu-Kai; Lai, Chi-Chun; Chuang, Lan-Hsin (Frontiers in Medicine, 2022)
Background: Evidence regarding the impact on visual field (VF), intraocular pressure (IOP), and antiglaucoma medications from trabeculectomy with antimetabolites for normal tension glaucoma (NTG) is conflicting because of insufficient study sample sizes. The aim of the study is to systematically assess the VF progression rate, IOP control and antiglaucoma medication use after trabeculectomy with antimetabolites for progressing NTG. Methods: We searched published articles on PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials from database inception to March 21, 2022. Study Selection: We selected studies that reported VF data before and after trabeculectomy with antimetabolite agents for NTG. We followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses reporting guidelines. Data were extracted by 2 independent reviewers, and a random-effects model was employed for the meta-analysis. Study outcomes were VF progression rates measured using the pooled mean deviation (MD) slope, changes in antiglaucoma medications, and IOP. Subgroup analyses of the MD slope according to mean and median age (65 and 65 years), baseline MD (−12 and −12 dB), and baseline IOP (15 and 15 mmHg) were performed to determine the results’ robustness. Results: We included 7 retrospective observational studies (Japan: 6 studies, USA: 1 study) comprising a total of 166 eyes. Mean preoperative VF MD slopes ranged from −0.52 to −1.05 dB/year. The meta-analysis demonstrated significant MD slope improvement after trabeculectomy (pooled mean difference: 0.54 dB/year, 95% CI: 0.40 to 0.67, I2 = 9%). Median age, baseline MD, and baseline IOP subgroup analyses revealed MD slope results were consistent with those of the main analyses. The mean IOP (pooled mean difference: −5.54 mmHg, 95% CI −6.02 to −5.06, I2 = 0%) and mean number of antiglaucoma medications (pooled mean difference: −1.75 mmHg, 95% CI: −2.97 to −0.53, I2 = 98%) significantly decreased after trabeculectomy. The most frequently reported early complications after trabeculectomy were hypotony, hyphema, and shallow anterior chamber. Conclusions: This systematic review and meta-analysis indicated that trabeculectomy with antimetabolites is beneficial for progressing NTG; it preserves visual function by alleviating the MD slope and reducing antiglaucoma medication use. However, several post-trabeculectomy complications should be monitored.